2010
DOI: 10.1002/clc.20533
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of the Dilated Phase of Hypertrophic Cardiomyopathy in Comparison With Those of Dilated Cardiomyopathy

Abstract: Patients with D-HCM were more symptomatic at diagnosis, although LV dilatation and impaired fractional shortening seemed more severe in patients with DCM. The prognosis for D-HCM patients was worse than that for patients with DCM despite similar or even more intensive treatment for heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 15 publications
4
26
0
1
Order By: Relevance
“…End-stage HCM, the stadium in which our patient was admitted to the hospital, is also characterized with higher incidence of ventricular arrhythmias and poor prognosis [7]. Of note, patients with end-stage HCM are more often male.…”
Section: Discussionmentioning
confidence: 89%
“…End-stage HCM, the stadium in which our patient was admitted to the hospital, is also characterized with higher incidence of ventricular arrhythmias and poor prognosis [7]. Of note, patients with end-stage HCM are more often male.…”
Section: Discussionmentioning
confidence: 89%
“…[1][2][3]17,18) Although LV systolic function is supernormal or preserved in most cases of HCM, progression to systolic impairment occurs in about 5-10% of patients when they are followed for a long period. [4][5][6][7][8][9] It is usually associated with LV remodeling with wall thinning and cavity dilatation, resembling the morphologic features of dilated cardiomyopathy (DCM). [4][5][6][7][8][9] Although this subtype of HCM, so-called D-HCM, has been reported to have a poor prognosis, some patients with D-HCM survive for a relatively long period in the current era of advanced arrhythmia and heart failure management.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] It is usually associated with LV remodeling with wall thinning and cavity dilatation, resembling the morphologic features of dilated cardiomyopathy (DCM). [4][5][6][7][8][9] Although this subtype of HCM, so-called D-HCM, has been reported to have a poor prognosis, some patients with D-HCM survive for a relatively long period in the current era of advanced arrhythmia and heart failure management. 2,11) In the present study, less LV enlargement at diagnosis of D-HCM and presence of significant MR during follow-up were associated with markedly worse clinical outcome, although cardiovascular mortality was originally poor in the whole cohort of D-HCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that CRT might be useful in a subset of D-HCM patients with wide QRS prolongation and LV dyssynchrony (30)(31)(32). Sustained or non-sustained ventricular tachycardia is frequently seen in D-HCM patients, and sudden death often occurs in the presence of severe heart failure (33). Several reports have noted that the observation of late gadolinium enhancement on MRI, presumed to represent fibrosis and replacement scarring, was probably largely responsible for the malignant ventricular tachyarrhythmias observed in these patients (34)(35)(36).…”
Section: Arg835leumentioning
confidence: 99%